The TRPM4 channel inhibitor 9-phenanthrol alleviates cerebral edema after traumatic brain injury in rats - Ma, Ping; Huang, Ning; Tang, Jun; Zhou, Zunjie; Xu, Jing; Chen, Yi; Zhang, Maoxin; Huang, Qin; Cheng, Yuan (Frontiers in Pharmacology, 2023)
Cerebral edema (CE) exerts an important effect on brain injury after traumatic brain injury (TBI). Upregulation of transient receptor potential melastatin 4 (TRPM4) in vascular endothelial cells (ECs) results in damage to capillaries and the blood-brain barrier (BBB), which is critical for the development of CE. Many studies have shown that 9-phenanthrol (9-PH) effectively inhibits TRPM4. The current study aimed to investigate the effect of 9-PH on reducing CE after TBI. In this experiment, we observed that 9-PH markedly reduced brain water content, BBB disruption, proliferation of microglia and astrocytes, neutrophil infiltration, neuronal apoptosis and neurobehavioral deficits. At the molecular level, 9-PH significantly inhibited the protein expression of TRPM4 and MMP-9, alleviated the expression of apoptosis-related molecules and inflammatory cytokines, such as Bax, TNF-α and IL-6, near injured tissue, and diminished serum SUR1 and TRPM4 levels. Mechanistically, treatment with 9-PH inhibited activation of the PI3K/AKT/NF-kB signaling pathway, which was reported to be involved in the expression of MMP-9. Taken together, the results of this study indicate that 9-PH effectively reduces CE and alleviates secondary brain injury partly through the following possible mechanisms: ①9-PH inhibits TRPM4-mediated Na + influx and reduces cytotoxic CE; ②9-PH hinders the expression and activity of MMP-9 by inhibiting the TRPM4 channel and decreases disruption of the BBB, thereby preventing vasogenic cerebral edema. ③9-PH reduces further inflammatory and apoptotic damage to tissues.